Development of Chemistry’s Learning Module Oriented Local Wisdom of Central Sulawesi for High School in Basic Acid Solution Materials - Hety E. Panambulo; Ratman Ratman; Nurida Nurida (Universitas Tadulako, 2022)
Development research has been carried out to produce a high school chemistry learning module that oriented Central Sulawesi’s local wisdom in acid-base solutions. This research was conducted using research and development (R&D) methods. The goal of this study was to ascertain the validity and applicability of the developed learning modules. Development of the learning module is expected to be used by teachers as users and for students in their independent learning, increasing the understanding of concepts and getting to know local wisdom in the Central Sulawesi region. The validity of the learning module was determined by a validation test conducted by specialists in the topic, medium, and user. In contrast, the practicality of the learning module was determined by the outcomes of the module's implementation by students. The validation results showed that the average score of the material expert of 2,66 was categorized as “valid,” the average score of the media expert was 3,29 with the category “valid,” and the average score of the user was 3,53 with the category “valid.” The results implementation of learning modules using students' response questionnaires obtained respectively, a percentage of 29% of students responded was “very practical,” 64,4% of students responded war “practical,” 6% of students responded was “impractical,” and 0% of students respond was “very impractical.” Based on these results, it can be concluded that the development module was “valid” and “practical” in using the learning process.